The Compatibility of Speaking Politeness Introduced in Conversation Texts in MTs English Textbook Grade VIII With The Standard of Content - Ulin Nuha (Al Hikmah: Journal of Education, 2025)
This study focuses on the issues: social contextual factors approach which analyzes the participants in the interaction and the communicative situation and politeness which analyzes the respect that an individual has for himself or herself, and maintaining the "self-esteem" in public or in private situations. This is a qualitative study. The data of this study are conversation texts. Units of analysis in this study are texts. The texts were analyzed based on the social contextual factors and politeness. In calculating the data and the final result of data percentage, quantification will be used to support this study. The result shows that there are two politeness strategies that occurred in the conversation texts, positive and negative. The speech functions of the transactional conversation texts are 54.5% matching the standard of content, the speech functions of the interpersonal conversation texts are 2.1% matching the standard of content, the linguistic feature applied in the transactional and interpersonal conversation texts uses the linguistic feature in functional literacy level, the speech functions of conversation texts introduced in EOS English on Sky 2 for junior high school grade VIII are less compatible with the standard of content based on the compatibility levels. This shows that this textbook's choice is less appropriate for users who emphasize interpersonal conversation texts.